Bionic lignin-based saline-alkali soil improvement material and preparation method thereof
By modifying lignin to prepare saline-alkali land improvement materials with pH and sodium ion responses, the problem of insufficient stability and responsiveness of existing materials in saline-alkali land improvement is solved, and intelligent improvement effects of soil structure improvement and salinity regulation are achieved.
Patent Information
- Application Number
- CN202511658033.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-11-13
- Publication Date
- 2025-12-09
- Estimated Expiration
- 2045-11-13
AI Technical Summary
Existing lignin-modified materials suffer from poor stability and insufficient responsiveness in saline-alkali land improvement, failing to effectively improve soil structure and dynamic changes in sodium ion concentration.
By simulating the balanced charge distribution of glutenin and the self-repairing function of sodium disulfide ions, lignin was modified by aqueous solution polymerization. Sulfonic acid anions and quaternary ammonium salt cationic monomers were introduced and combined with multi-thiol monomers to prepare lignin-based saline-alkali land improvement materials with pH and sodium ion responses.
It achieves intelligent response of materials under different saline-alkali environments, effectively neutralizes soil charge, flocculates clay particles, fixes sodium ions, improves soil structure, breaks up compaction, reduces salinity, and adapts to the soil improvement needs of areas with different salinity intensities.
Smart Images

Figure CN121086155A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the technical field of high molecular materials and soil improvement, in particular to a biomimetic lignin-based saline-alkali soil improvement material and a preparation method thereof. BACKGROUND
[0002] Soil salinization is an important manifestation of soil degradation, which seriously harms agricultural production, ecological safety and human health. The core challenge of saline-alkali soil improvement lies in the excessive sodium ions and high pH value in the soil, which easily leads to soil structure hardening, reduced air and water permeability, and nutrient imbalance, and causes ion toxicity and osmotic stress to plant growth.
[0003] In a high-salt environment, a large number of cations will shield the electrostatic interaction between the high-molecular soil conditioner and the soil particles, greatly reducing their charge neutralization and bridging ability; under high pH conditions, the ionization of some functional groups will be inhibited, reducing their effective action radius and failing to function. At the same time, the dry-wet alternating process of "drought and salt return" and "rainy season leaching" is common in saline-alkali soil. Water-retaining agents such as polyvinyl alcohol cannot inhibit water evaporation during the dry season, leading to salt accumulation on the surface; some desalination-type high-molecular soil conditioners, such as natural polysaccharides grafted with carboxyl groups, can adsorb sodium ions through ion exchange, but they are easily leached by rainwater in the rainy season, resulting in the "desalination and salt return" phenomenon.
[0004] To break through this bottleneck, an intelligent saline-alkali soil improvement material that is both stable in saline-alkali conditions and can respond to the environment is needed. Natural polymers have become a rational substrate due to their advantages such as wide sources, easy functionalization and modification, and biodegradability. Lignin, as a natural three-dimensional polymer with abundant reserves and low cost, has its own structural heterogeneity and non-uniformity, low reactivity, complex functional groups, and poor solubility and compatibility, which limits its efficient use. Currently, lignin modification for water-retaining agents, flocculants and soil conditioners mostly uses simple mixed copolymerization. For example, patent (CN115772267A) crosslinks the emulsion of amphoteric ions obtained by reacting lignin sulfonate and quaternary ammonium salt with polyvinyl alcohol, mainly for water retention and sand particle adhesion. Patent (CN112537989A) prepares a hydrophilic resin by copolymerizing lignin sulfonate with anionic acrylic acid, humic acid, etc., the polymerization reaction is mixed polymerization, and the material itself is not soluble in water. Both of them focus on water retention, and the charge type is single, which is difficult to achieve charge neutralization and metal ion exchange of saline-alkali soil through high-density positive and negative charges. Another patent (CN113831480A) modifies lignin with itaconic acid and quaternary ammonium salt cations, which uses its charge neutralization as a crude oil wastewater demulsifier. However, the molecular structure of itaconic acid contains two carboxyl groups, which easily forms steric hindrance, reducing its grafting efficiency on lignin. In addition, carboxylic acid groups in high-salt environments of saline-alkali soil are easily attacked by Cl - , SO42- The equivalent ion effect inhibits dissociation to cause charge neutralization ability to decrease, and the above material cannot precisely control polymer polarity through molecular regulation, and has no sodium ion responsiveness, and is not suitable for saline-alkali land improvement. Patent (CN120459954A) modifies acetic acid-hydrogen peroxide modified lignin into a gel with acrylic acid for crosslinking to be used as a saline-alkali land sodium ion adsorbent. The material cannot perceive dynamic changes of soil sodium ion concentration, lacks responsiveness, affects precision and sustainability of its adsorption, and in addition, the gel mainly focuses on sodium ion removal, fails to simultaneously improve soil aggregates and structure, has a single function, and is difficult to meet the needs of comprehensive improvement of saline-alkali land. SUMMARY
[0005] Based on the defects in the prior art, the present application provides a biomimetic lignin-based saline-alkali land improvement material and a preparation method. The present application innovatively simulates the charge distribution of wheat gluten and the sodium ion self-repairing function of disulfide bond, and develops a saline-alkali land improvement material with lignin pH and sodium ion environment response and cooperative repair mechanism.
[0006] The present application first provides a preparation method of a lignin-based saline-alkali land improvement material, which comprises the following steps: The lignin and / or lignin derivative is modified with a sulfonic acid anion monomer and a quaternary ammonium salt cation monomer by aqueous solution polymerization to obtain an amphiphilic anion-cation lignin composite system solution, and a multi-thiol monomer is introduced by click chemistry to prepare the lignin-based saline-alkali land improvement material.
[0007] In the above preparation method, the lignin derivative is at least one of calcium lignosulfonate, sodium lignosulfonate, magnesium lignosulfonate, potassium lignosulfonate, ammonium lignosulfonate, alkali lignin, sulfate lignin, groundwood lignin, alkylated lignin, aminated lignin, hydroxymethylated lignin, acetylated lignin and oxidized lignin; The sulfonic acid anion monomer is at least one of 2-acrylamido-2-methylpropanesulfonic acid, acrylamide tert-butyl sulfonic acid, 2-(methacryloyloxy)ethyl dimethyl-(3-sulfopropyl) ammonium hydroxide, sulfopropyl methacrylate, sodium methacrylate sulfonate, sodium acrylate sulfonate, 3-allyloxy-2-hydroxypropane sulfonic acid sodium, 3-sulfopropyl potassium acrylate, 3-methacrylic acid sulfopropyl potassium salt, sodium vinyl sulfonate and sodium p-styrene sulfonate; The quaternary ammonium salt cationic monomer is at least one of methacryloyloxyethyl trimethyl ammonium chloride, dimethyldiallyl ammonium chloride, acryloyloxyethyl trimethyl ammonium chloride, methacrylamidopropyl trimethyl ammonium chloride, benzyl vinyl trimethyl ammonium chloride, methacryloyloxyethyl dimethyl benzyl ammonium chloride, N-cetyl-N,N-dimethyl benzyl ammonium chloride, 2-acrylamidoethyl dimethyl dodecyl ammonium bromide, allyl trimethyl ammonium chloride and hydroxypropyl trimethyl ammonium chloride chitosan; The polythiol monomer is at least one of trimethylolpropane tris (3-mercaptopropionate), tetra (3-mercaptopropionate) pentaerythritol ester, ethylene glycol di (3-mercaptopropionate), trimethylolpropane tris (2-mercaptoacetate), pentaerythritol tetramercaptoacetate and dipentaerythritol hexa (3-mercaptopropionate).
[0008] The preparation method specifically comprises the following steps: S1, adjusting the pH value of the lignin and / or lignin derivative solution, heating; dividing the quaternary ammonium salt cationic monomer solution into two parts by volume, and adding one part to the lignin and / or lignin derivative solution; dividing the oxidizing agent and reducing agent solutions into three parts by weight, adding one part of the oxidizing agent solution to the above solution, then adding one part of the reducing agent solution, and reacting; S2, dividing the sulfonic acid anion monomer solution into two parts by volume, adding one part of the sulfonic acid anion monomer solution to the system obtained in S1, and reacting; then adding another part of the quaternary ammonium salt cationic monomer solution, adding one part of the oxidizing agent solution, adding one part of the reducing agent solution, and finally adding another part of the sulfonic acid anion monomer solution, and reacting; to obtain a lignin anion-cation composite system solution; S3, mixing the polythiol monomer solution and the lignin anion-cation composite system solution, adding one part of the oxidizing agent solution, then adding one part of the reducing agent solution, and reacting, to obtain the lignin-based saline-alkali soil improvement material after drying.
[0009] In the above preparation method, the mass percentage concentration of the lignin and / or lignin derivative solution is 5%-35%; The solvent of the lignin and / or lignin derivative solution is water; The mass percentage concentration of the quaternary ammonium salt cationic monomer solution is 60%-80%; and the solvent of the quaternary ammonium salt cationic monomer solution is water; The oxidizing agent is at least one of ammonium persulfate, potassium persulfate, sodium persulfate and hydrogen peroxide; The reducing agent is at least one of ascorbic acid, sodium bisulfite, sodium sulfite and sodium thiosulfate; The mass percentage concentration of the oxidizing agent and reducing agent solution is 3%-15%; preferably 5%-10%; The mass percentage concentration of the sulfonic anion monomer solution is 30%-65%; the solvent of the sulfonic anion monomer solution is water; The mass percentage concentration of the multi-sulfhydryl monomer solution is 3.5%-30%; the solvent of the multi-sulfhydryl monomer solution is ethanol solution; The mass ratio of the total mass of the sulfonic anion monomer and the quaternary ammonium salt cationic monomer to the mass of the lignin and / or lignin derivative is 2-16:1; The mass ratio of the sulfonic anion monomer to the quaternary ammonium salt cationic monomer is 1:8 to 8:1; The total mass of the oxidizing agent and the reducing agent is 0.5%-5% of the total mass of the lignin and / or lignin derivative, the quaternary ammonium salt cationic monomer, the sulfonic anion monomer, and the multi-sulfhydryl monomer; preferably 1%-2%; The mass ratio of the oxidizing agent to the reducing agent is 1:1-1.5; The mass ratio of the lignin and / or lignin derivative to the multi-sulfhydryl monomer is 5-15:1.
[0010] In the above preparation method, when the mass ratio of the sulfonic anion monomer to the quaternary ammonium salt cationic monomer is in different ranges, the lignin-based saline-alkali soil improvement material exhibits completely different macroscopic physical states: When the mass ratio of the sulfonic anion monomer to the quaternary ammonium salt cationic monomer is 1:1.5 to 1.5:1, the lignin-based saline-alkali soil improvement material forms a stretchable gel state; When the mass ratio of the sulfonic anion monomer to the quaternary ammonium salt cationic monomer is between 1:1.5 to 1:8 (not including 1:1.5), the lignin-based saline-alkali soil improvement material forms a high-viscosity aqueous solution; When the mass ratio of the sulfonic anion monomer to the quaternary ammonium salt cationic monomer is between 1.5:1 to 8:1 (not including 1.5:1), the lignin-based saline-alkali soil improvement material forms a low-viscosity aqueous solution.
[0011] In the above preparation method, in step S1, the pH of the lignin and / or lignin derivative solution is adjusted to 10-12 using a KOH solution; The heating temperature is 35-50℃; preferably 40℃-45℃ The reaction time is 1-2h; In step S2, the reaction time of adding one portion of the sulfonic anion monomer solution in the system obtained in S1 is 1-2h; The reaction time after adding another portion of the sulfonic anion monomer solution is 1-2h; In step S3, the reaction time is 2-4h.
[0012] In the above preparation method, the oxidant solution is added dropwise for 30 min, and then the reducing agent solution is added dropwise in steps S1, S2 and S3. In step S3, the multi-thiol monomer solution is added dropwise into the anion-cation lignin complex system solution at a flow rate of 0.5-15 mL / min.
[0013] The present application also provides a lignin-based saline-alkali soil improvement material prepared by the above preparation method.
[0014] The application of the above lignin-based saline-alkali soil improvement material in improving saline-alkali soil also falls within the protection scope of the present application.
[0015] Specifically, the saline-alkali soil has one or more of the following properties: (1) High pH value: the soil pH value is usually greater than 8.5, and can even reach above 9.0, showing strong alkalinity; (2) High exchangeable sodium content: the proportion of adsorbed sodium ions on the soil colloids is relatively high, and the sodium adsorption ratio is usually greater than 13, resulting in soil particle dispersion.
[0016] (3) Soil structure deterioration: due to the dispersion effect of sodium ions, the soil aggregate structure is destroyed, resulting in poor water and air permeability.
[0017] (4) Ion toxicity and nutrient imbalance: excessive sodium ions, chloride ions, carbonate / hydrogen carbonate ions in the soil solution directly poison the plant roots and inhibit the absorption of essential nutrients such as calcium and potassium.
[0018] In the above application, according to the lignin-based saline-alkali soil improvement material obtained by reacting the sulfonic anion monomer and the quaternary ammonium salt cation monomer in different mass ratios, the following application methods and dosages are used: 1) When the mass ratio of the sulfonic anion monomer to the quaternary ammonium salt cation monomer is 1:1.5 to 1.5:1, the material is directly applied to the soil as a soil conditioner or used as a coating material; wherein the application amount of the soil conditioner is 40-200 kg / acre, and the application amount of the coating material is 3%-20% of the total mass of the coated fertilizer.
[0019] 2) When the mass ratio of the sulfonic anion monomer to the quaternary ammonium salt cation monomer is 1:8 to 1:1.5, the obtained material is configured into an aqueous solution and used for foliar spraying or drip irrigation; for foliar spraying, the concentration is configured to be 0.5%-2%, and the dosage is 20-50 kg / acre; for drip irrigation, the concentration is 0.01-2%, and the dosage is 20-150 kg / acre.
[0020] 3) When the mass ratio of the sulfonic acid anion monomer to the quaternary ammonium salt cation monomer is 1.5:1 to 3:1, the obtained material is used as a seedling root dipping agent, and when used, it is diluted to a mass concentration of 0.1% to 0.3%, the roots of crops are soaked in the solution for 5 min, and then are planted.
[0021] The biomimetic lignin-based saline-alkali soil improvement material of the application has the following innovative design: (1) In the aqueous solution polymerization reaction system, the sequence and proportion of sulfonic acid groups and quaternary ammonium salt groups are precisely controlled by stepwise activation and alternating copolymerization, so that the positive and negative charges form a more uniform sequence distribution, and an amphiphilic ionic polymer with adjustable anion / cation ratio is prepared; (2) With the help of the polarity regulation of anion and cation on lignin, the thiol groups are limited and regularly arranged, so that the thiol-ene click chemistry reaction is efficiently completed, and a multifunctional thiol monomer is introduced; meanwhile, the chain transfer characteristics of the multi-thiol functional group are used to adjust the crosslinking degree of the material to meet the needs in different application scenarios; (3) The multi-thiol can shield the surface charge under high sodium ion concentration, reduce the electrostatic repulsion, make the chains close and oxidize to generate dynamic disulfide bonds, induce the crosslinking of the polymer to fix the sodium ions, and reduce the soil salinity; (4) The sulfonic acid group maintains stable negative charge to adsorb ions in the soil, and the quaternary ammonium salt group can effectively flocculate the negatively charged clay particles, and in the high saline-alkali environment, it maintains excellent charge neutralization and bridging ability, and can realize the response behavior of the material showing significant and reversible conformational transition in the pH range of 5 to 11.
[0022] In summary, the innovation of the application lies in designing and preparing a lignin-based intelligent biomimetic saline-alkali soil improvement material with pH and Na + response ability. This design finally realizes two key application functions and achieves synergistic improvement. Specifically, the advantages of the application are as follows: the quaternary ammonium salt group can efficiently neutralize and flocculate the negatively charged soil clay particles, the sulfonic acid group can reduce the soil salinity through Na + replacement, and the polymer long chain can play a bridging role to link small particles into stable large particles. Through "neutralization-bridging", the formation of soil aggregate structure is effectively promoted, the hardening is broken, the soil physical structure is fundamentally improved, and the soil salt washing and alkali removal are accelerated; in the high Na + environment, the multi-thiol oxidizes to generate dynamic disulfide bonds, which not only crosslink and fix the free Na + ions to reduce the soil soluble salt content, but also promote the formation of large aggregates through the bridging network; the material shows reversible conformational transition in the pH range of 5 to 11, and can intelligently regulate the charge exposure and crosslinking behavior according to the changes in the microenvironment of the saline-alkali soil, so as to ensure that the aggregate construction and salt regulation functions can be continuously exerted in different saline-alkali intensity regions. BRIEF DESCRIPTION OF DRAWINGS
[0023] Figure 1 Synthesis process of CaLS-AMPS / DMC / TMPMP prepared for Example 1.
[0024] Figure 2 Dynamic disulfide bond formation principle of CaLS-AMPS / DMC / TMPMP prepared for Example 1.
[0025] Figure 3 pH and sodium ion responsive morphology change diagram of CaLS-AMPS / DMC / TMPMP prepared for Example 1.
[0026] Figure 4 Macrograph and SEM diagram of CaLS-AMPS / DMC / TMPMP prepared for Examples 1-3.
[0027] Figure 5 Infrared spectrum of CaLS, DMC and CaLS-AMPS / DMC / TMPMP prepared for Example 1.
[0028] Figure 6 pH responsive macroscopic morphology diagram of CaLS-AMPS / DMC / TMPMP prepared for Examples 1-2.
[0029] Figure 7 Sodium ion responsive macroscopic morphology diagram of CaLS-AMPS / DMC / TMPMP prepared for Examples 1-2.
[0030] Figure 8 Soil flocculation effect diagram of saline-alkali soil improvement material prepared for Examples 1-3 and Comparative Examples 1-5.
[0031] Figure 9 Comparison diagram of soil column leaching amount and infiltration time under different treatment conditions.
[0032] Figure 10 Effect of lignin-based saline-alkali soil improvement material on potting soil properties. DETAILED DESCRIPTION
[0033] The application will be further described in conjunction with the specific embodiments, and the examples given are only for illustrating the application, not for limiting the scope of the application.
[0034] The experimental methods in the following examples are all conventional methods, unless otherwise specified.
[0035] The quantitative tests in the following examples are all set up with three repeated experiments, and the results are averaged, unless otherwise specified.
[0036] The materials, reagents, etc. used in the following examples, unless otherwise specified, can be obtained commercially.
[0037] Example 1 A solution of calcium lignosulfonate (CaLS) with a mass concentration of 10% (solvent: deionized water) was prepared in a volume of 500 mL and then transferred to a reactor. The pH of the above-mentioned calcium lignosulfonate solution was adjusted to 10.3 using a 1M KOH solution, heated to 45°C, and continuously bubbled with nitrogen for 30 min. 67 mL of a 75wt% DMC solution (methacryloyloxyethyltrimethylammonium chloride, solvent: water) was added dropwise to the above-mentioned reaction system. 1.6 g of oxidant ammonium persulfate and 1.6 g of reducing agent ascorbic acid were separately dissolved in 30 mL of deionized water and divided into three equal parts by weight. One part of the ammonium persulfate solution was added dropwise to the reactor, and 30 min later, one part of the ascorbic acid solution was added. The reaction was carried out for 1.5 h. 50 g of 2-acrylamido-2-methylpropanesulfonic acid (AMPS) was dissolved in 100 mL of ionized water, and 50% of the total volume of the above-mentioned prepared AMPS solution was added to the above-mentioned reactor. The reaction was carried out for 1.5 h. 67 mL of a 75wt% DMC solution (methacryloyloxyethyltrimethylammonium chloride, solvent: water) was added to the system, one part of the ammonium persulfate solution was added dropwise, 30 min later, one part of the ascorbic acid solution was added, and the remaining AMPS solution was added to the system. The reaction was carried out for 1.5 h to obtain a cation-anion lignin composite system solution. 5 g of trimethylolpropane tris(3-mercaptopropionate) was dissolved in 70 mL of 95% (v / v) ethanol solution to obtain a trimethylolpropane tris(3-mercaptopropionate) solution. The trimethylolpropane tris(3-mercaptopropionate) solution was added to the above-mentioned solution at a flow rate of 2 mL / min. The remaining ammonium persulfate solution was added dropwise, 30 min later, the remaining ascorbic acid solution was added, and the reaction was carried out for 2.5 h to end the experiment. The above-mentioned reaction mixture was cooled to room temperature and dried in a 60°C oven to obtain a biomimetic lignin-based saline-alkali soil improvement material (CaLS-AMPS / DMC / TMPMP).
[0038] Example 2 The preparation method was the same as that of Example 1, except that “67 mL of a 75wt% DMC solution” in Example 1 was replaced with “34 mL of a 75wt% DMC solution”, “50 g of AMPS” was replaced with “100 g of AMPS”, “70 mL of 95% anhydrous ethanol” was replaced with “20 mL of 95% anhydrous ethanol”, and “added dropwise to the above-mentioned solution at a flow rate of 2 mL / min” was replaced with “added dropwise to the above-mentioned solution at a flow rate of 0.7 mL / min”.
[0039] Example 3 The preparation method of Example 1 is the same, except that "67 mL of 75 wt% DMC solution" in Example 1 is replaced with "62.5 mL of 80 wt% DAC solution (acryloyloxyethyl trimethyl ammonium chloride, solvent is water)"; "50 g AMPS" is replaced with "100 g AMPS"; "70 mL of 95% anhydrous ethanol" is replaced with "45 mL of 95% anhydrous ethanol", and "is added to the above solution at a flow rate of 2 mL / min" is replaced with "is added to the above solution at a flow rate of 1.5 mL / min".
[0040] Comparative Example 1 This comparative example is the same as the raw material type and mass in Example 1, and the main process difference is: no alternating copolymerization is performed. CLS, AMPS and DMC are simultaneously added to the reaction kettle at the beginning of the reaction, and the oxidant and the reducing agent are added to the reaction system in three times, with a 1.5 h interval between each time.
[0041] The specific preparation method is as follows: A 500 mL solution of calcium lignosulfonate (CaLS) with a mass concentration of 10% is prepared, then transferred to a reactor, and the pH of the above calcium lignosulfonate solution is adjusted to 10.3 with 1M KOH solution. Heat to 45°C, continuously pass nitrogen for 30 min, add 134 mL of 75 wt% DMC solution (methyl methacryloyloxyethyl trimethyl ammonium chloride, solvent is water) to the above reaction system, then dissolve 50 g of 2-acrylamido-2-methylpropanesulfonic acid (AMPS) in 100 mL of ionized water and add it to the above reaction system. Dissolve 1.6 g of oxidant ammonium persulfate and 1.6 g of reducing agent ascorbic acid in 30 mL of deionized water, respectively, and divide them into three equal parts by weight. First, add one part of the ammonium persulfate solution dropwise to the reactor, then add one part of the ascorbic acid solution dropwise after 30 min, and react for 1.5 h. Then add one part of the ammonium persulfate solution, and after 30 min, add one part of the ascorbic acid solution, and react for 1.5 h to obtain a cationic lignin composite system solution. Dissolve 5 g of trimethylolpropane tris (3-mercaptopropionate) in 70 mL of 95% (v / v) ethanol solution to obtain a trimethylolpropane tris (3-mercaptopropionate) solution, then add the trimethylolpropane tris (3-mercaptopropionate) solution to the above solution at a flow rate of 2 ml / min, add the remaining ammonium persulfate solution, and after 30 min, add the remaining ascorbic acid solution. React for 2.5 h to complete the experiment. Cool the above reaction mixture to room temperature, dry in a 60°C oven, and obtain a lignin-based saline-alkali soil improvement material.
[0042] Comparative Example 2 The main process difference is that the step-by-step activation is not performed. When the reaction system is heated to 45°C, ammonium persulfate (oxidizing agent) and ascorbic acid (reducing agent) are directly added.
[0043] The specific preparation method is as follows: A 500 mL solution of calcium lignosulfonate (CaLS) with a mass concentration of 10% is prepared and then transferred to a reactor. The pH of the above-mentioned calcium lignosulfonate solution is adjusted to 10.3 with a 1M KOH solution, heated to 45°C, and continuously purged with nitrogen for 30 min. 67 mL of 75wt% DMC solution (methyl acryloyloxyethyl trimethyl ammonium chloride, solvent is water) is added dropwise to the above-mentioned reaction system. 1.6 g of oxidizing agent ammonium persulfate and 1.6 g of reducing agent ascorbic acid are dissolved in 30 mL of deionized water, respectively. The ammonium persulfate solution is added dropwise to the reactor, and the ascorbic acid solution is added dropwise after 30 min. The reaction is carried out for 1.5 h. 50 g of 2-acrylamido-2-methylpropanesulfonic acid (AMPS) is dissolved in 100 mL of ionized water. 50% of the total volume of the above-mentioned prepared AMPS solution is added to the above-mentioned reactor, and the reaction is carried out for 1.5 h. 67 mL of 75wt% DMC solution (methyl acryloyloxyethyl trimethyl ammonium chloride, solvent is water) is added to the system, and the remaining AMPS solution is added to the system. The reaction is carried out for 1.5 h to obtain an anion-cation lignin composite system solution. 5 g of trimethylolpropane tris (3-mercaptopropionic acid) is dissolved in 70 mL of 95% (v / v) ethanol solution to obtain a trimethylolpropane tris (3-mercaptopropionic acid) solution. The trimethylolpropane tris (3-mercaptopropionic acid) solution is added to the above-mentioned solution at a flow rate of 2 ml / min. The reaction is carried out for 2.5 h and then the experiment is stopped. The above-mentioned reaction mixture is cooled to room temperature and dried in a 60°C oven to obtain a lignin-based saline-alkali soil improvement material.
[0044] Comparative Example 3 The difference between this comparative example and Example 1 is that AMPS is replaced with the same mass of itaconic acid. The other preparation methods and raw materials are the same as those of Example 1.
[0045] Comparative Example 4 The difference between this comparative example and Example 1 is that no sulfonic acid group anion monomer solution is introduced, only a quaternary ammonium salt cationic monomer solution is introduced.
[0046] The specific preparation steps are as follows: A solution of calcium lignosulfonate (CaLS) with a concentration of 10% was prepared in 500 mL, and then transferred to a reactor. The pH of the solution was adjusted to 10.3 using a 1 M KOH solution. The solution was heated to 45°C, and nitrogen was continuously bubbled into the solution for 30 min. 134 mL of a 75 wt% DMC solution (methacryloyloxyethyltrimethylammonium chloride, solvent: water) was added dropwise to the solution. 1.6 g of an oxidizing agent, ammonium persulfate, and 1.6 g of a reducing agent, ascorbic acid, were separately dissolved in 30 mL of deionized water, and each was divided into three equal parts. One part of the ammonium persulfate solution was added dropwise to the reactor, and 30 min later, one part of the ascorbic acid solution was added dropwise. The reaction was allowed to proceed for 1.5 h. 134 mL of a 75 wt% DMC solution (methacryloyloxyethyltrimethylammonium chloride, solvent: water) was added dropwise to the solution. One part of the ammonium persulfate solution was added dropwise, and 30 min later, one part of the ascorbic acid solution was added dropwise. The reaction was allowed to proceed for 1.5 h to obtain a lignin copolymer solution. 5 g of trimethylolpropane tris(3-mercaptopropionate) was dissolved in 70 mL of a 95% ethanol solution to obtain a trimethylolpropane tris(3-mercaptopropionate) solution. The trimethylolpropane tris(3-mercaptopropionate) solution was added dropwise to the lignin copolymer solution. The remaining ammonium persulfate solution was added dropwise, and 30 min later, the remaining ascorbic acid solution was added dropwise. The reaction was allowed to proceed for 2.5 h, and the experiment was then terminated. The reaction mixture was cooled to room temperature, and was dried in an oven at 60°C to obtain a lignin-based saline-alkaline soil improvement material.
[0047] Comparative Example 5 The difference between this comparative example and Example 1 is that no quaternary ammonium salt cationic monomer solution was introduced, and only a sulfonic acid anionic monomer solution was introduced.
[0048] The specific preparation steps are as follows: A solution of calcium lignosulfonate (CaLS) with a concentration of 10% was prepared in 500 mL of deionized water and then transferred to a reactor. The pH of the solution was adjusted to 11 using a 1 M KOH solution, and the solution was heated to 45 °C. Nitrogen gas was continuously bubbled into the solution for 30 min. 100 g of 2-acrylamido-2-methylpropanesulfonic acid (AMPS) was dissolved in 200 mL of deionized water, and a 50 wt% solution of AMPS was added to the reactor. 1.6 g of the oxidizing agent ammonium persulfate and 1.6 g of the reducing agent ascorbic acid were each dissolved in 30 mL of deionized water and divided into three equal parts by weight. One part of the ammonium persulfate solution was added dropwise to the reactor, and 30 min later, one part of the ascorbic acid solution was added dropwise. The reaction was allowed to proceed for 1.5 h. The remaining 50 wt% solution of AMPS was then added to the system, and one part of the ammonium persulfate solution was added dropwise. After 30 min, one part of the ascorbic acid solution was added dropwise, and the reaction was allowed to proceed for 1.5 h. A solution of trimethylolpropane tris(3-mercaptopropionate) was prepared by dissolving 5 g of trimethylolpropane tris(3-mercaptopropionate) in 70 mL of 95% ethanol. The solution was then slowly added dropwise to the lignin copolymer solution. The remaining ammonium persulfate solution was added dropwise, and 30 min later, the remaining ascorbic acid solution was added dropwise. The reaction was allowed to proceed for 2.5 h, and then the experiment was terminated. The reaction mixture was cooled to room temperature and dried in an oven at 60 °C to obtain the lignin-based saline-alkaline soil improvement material.
[0049] Example 4 I. Material synthesis mechanism Figure 1 The synthesis process of the CaLS-AMPS / DMC / TMPMP prepared in Example 1. The synthesis mechanism of the material mainly includes two core steps: modification of lignin with anions and cations and introduction of thiol monomers through click chemistry. First, the water-soluble initiator ammonium persulfate (APS) and ascorbic acid undergo an oxidation-reduction reaction to generate strong oxidizing sulfate radical anions (SO4 -) and hydroxyl radical (HO•). First, cationic monomer DMC is added, and the free radicals in the system will preferentially attack the carbon-carbon double bond on the DMC molecule to generate DMC monomer radicals through addition reaction. The generated DMC radicals copolymerize with the phenolic oxygen radicals generated on the CaLS skeleton due to radical attack, and the DMC branches are grafted onto the lignin skeleton through chain growth, increasing the solubility of lignin; then, anionic monomer AMPS is added, at this time, various free radicals in the system attack the carbon-carbon double bond of AMPS to generate AMPS monomer radicals or make the polymer chain end become AMPS unit; finally, through the free radical copolymerization mechanism, DMC and AMPS are grafted onto the same lignin molecule to form an amphoteric copolymer (CLS-AMPS / DMC) with positive and negative charges. Trimethylolpropane tris (3-mercaptopropionate) with a terminal mercapto group (-SH) is added to the above amphoteric polymer system, and the DMC monomer and AMPS unsaturated olefinic bond grafted on the polymer chain are regulated by the polarity of the above material to facilitate the limited and regular arrangement of the mercapto group. These olefinic bonds and the mercapto group (-S) on trimethylolpropane tris (3-mercaptopropionate) undergo efficient "thiol-ene" click chemistry reaction. Figure 2 For the principle of dynamic disulfide bond formation, the mercapto groups on the trimethylolpropane tris (3-mercaptopropionate) can shield the surface charge of the material under high sodium ion concentration, reduce the electrostatic repulsion, and allow the chains to approach and oxidize to form dynamic disulfide bonds (-S-S-). Figure 3 The responsive change mechanism of the material under pH and sodium ion stimulation is shown. Under high pH conditions, the negative charge of the sulfonic acid group produces strong electrostatic attraction with the quaternary ammonium salt cation group in the molecular chain, causing the polymer chain to change from an extended conformation to a contracted and curled state. This conformational change further promotes the intermolecular combination through hydrophobic interaction, enhancing the adsorption and wrapping ability of soil particles, thereby promoting the formation of stable soil microaggregates. In terms of sodium ion response, the mercapto groups introduced into the material can approach and oxidize to form disulfide bonds through electrostatic shielding in a high sodium ion concentration environment, causing the polymer network to aggregate and effectively fixing sodium ions.
[0050] II. Material characterization 1. Macroscopic physical state and scanning electron microscope (SEM) Figure 4 The macroscopic state and SEM images of the biomimetic lignin-based saline-alkali soil improvement material prepared in Examples 1-3 are shown in Figure 1 and Figure 2, respectively. Figure 4 From Figure 1 (1), the macroscopic physical state of the materials with different ratios can be observed. Example 1 is in a high-viscosity aqueous solution state, Example 2 is in a low-viscosity aqueous solution state, and Example 3 is in a stretchable gel state. In order to better observe the surface morphology of the material, Figure 2 (1) is a SEM image of Example 1, Figure 2 (2) is a SEM image of Example 2, and Figure 2 (3) is a SEM image of Example 3. Figure 4The SEM image in (2) can be seen that the three-dimensional network of the bionic lignin-based saline-alkali soil improvement material prepared in Example 1 is dense and continuous, the pore size is small and uniform, the wall thickness is high and the crosslinking points are many, and a compact structure is presented, reflecting high entanglement and high cohesion. Compared with Example 1, the structure of Example 2 is relatively loose, the pore size is large and the distribution is uneven, the wall is thin and smooth, and the crosslinking points are few; a three-dimensional porous network structure is formed in Example 3, which is a typical gel morphology, the pore wall is relatively thick, and the structure is coherent.
[0051] 2. Fourier infrared spectrum Figure 5 Functional groups of CaLS, DMC and CaLS-AMPS / DMC / TMPMP prepared in Example 1 were determined by Fourier transform infrared spectrum analysis. Compared with the Fourier transform infrared spectrum of CaLS, CaLS-AMPS / DMC / TMPMP appeared new peaks at 2570, 1726, 1640, 1480 and 950 cm -1 The stretching vibration peak at 2570 cm -1 is a thiol group (S-H), and the successful introduction of surface polythiol monomer. The stretching vibration peak at 1726 cm -1 is due to the introduction of carbonyl (C=O) in DMC. The characteristic absorption peak at 1640 cm -1 is the characteristic absorption peak of amide group belonging to amide I band, which confirms the existence of amide group; at the same time, the characteristic absorption peak at 1038 cm -1 is enhanced, indicating the increase of sulfonic acid group content. The coexistence of these two key characteristic peaks strongly proves that AMPS is successfully introduced into the copolymer. The characteristic absorption peaks at 1480 and 950 cm -1 correspond to the bending vibration of -CN adjacent to quaternary ammonium in DMC monomer and the stretching vibration of -CH2-N + (CH3)3, which indicates the successful graft copolymerization of surface quaternary amine group, the successful construction of zwitterionic polymer on the surface and the successful introduction of mercapto monomer.
[0052] 3. Cationic degree, anionic degree and intrinsic viscosity The cationic degree was measured according to the national standard GB / T 31246-2014, and the anionic degree and intrinsic viscosity of the material were measured according to the national standard GB / T 17514-2017. The results are shown in Table 1 below.
[0053]
[0054] From Table 1, it can be seen that by stepwise and alternating copolymerization of quaternary ammonium salt monomer and sulfonic acid anion monomer, the cationic group and anionic group are regularly and efficiently introduced into the lignin molecular chain, so that the thiol can be fully exposed to realize the limited position and regular arrangement, thereby efficiently completing the thiol-ene click chemistry reaction. In comparison, in Comparative Example 1, the simultaneous feeding of all monomers leads to a large amount of copolymerization due to the reactivity ratio, resulting in a decrease in grafting rate and molecular weight. In Comparative Example 2, the simultaneous addition of the initiator leads to intermolecular random crosslinking due to the high radical concentration, both of which significantly reduce the effective ion degree and molecular weight of the material. In Comparative Example 3, itaconic acid is used to replace AMPS, which has poor water solubility and solubility in organic materials. The molecular structure contains two carboxyl groups, and the space structure between the two carboxyl groups is hindered. This hindrance will be more obvious during polymerization, making it difficult to contact with the remaining itaconic acid, resulting in low grafting copolymerization efficiency, low anionic degree and low intrinsic viscosity. Comparative Example 4 is a pure cationic monomer polymerization, and Comparative Example 5 is a pure anionic polymerization, both of which destroy the charge balance of the material design and lose the advantage of the synergistic effect of anions and cations. Due to the inability to regulate the polarity of lignin, the multi-thiol reaction efficiency is low.
[0055] III. Material responsiveness test 1. pH responsiveness test In order to verify whether the lignin-based saline soil improvement material prepared in Examples 1-2 will undergo the expected chain conformation transition in different pH environments, the pH response behavior thereof was quantitatively characterized by determining the turbidity of the aqueous solution. The specific method is as follows: the lignin-based saline soil improvement material was prepared into a 0.01 g / mL solution, and then the pH value of each sample tube was precisely adjusted using 0.1M HCl solution or KOH solution to form a pH gradient, and the solution pH was adjusted to about 4, 6, 8, 10 and 12, respectively, to construct an experimental gradient under different pH conditions. The macroscopic morphology of the solution as the pH changes is shown in Figure 6 It can be seen from Figure 6 that when the pH is about 8, flocculent precipitates begin to appear in the solution of the lignin-based saline soil improvement material. With the further increase of the pH value, the flocculent substances gradually increase and enlarge, and finally form a three-dimensional network gel structure. This phenomenon indicates that the lignin-based saline soil improvement material prepared in Examples 1-2 has obvious response characteristics in different acid-base and ionic strength environments.
[0056] 2. Sodium ion response test 0.5 g of the lignin-based saline soil improvement material prepared in Examples 1-2 was dissolved in 10 mL of deionized water, and 5 mL of NaCl solution with a concentration of 10 g / L was added dropwise to observe the sodium ion response behavior.
[0057] The response behavior is shown in Figure 7As shown, flocculent precipitate can be observed in the solution after adding NaCl to the lignin-based saline-alkali soil material solution. This is because with the addition of NaCl, Na + The neutralization of the charge repulsion causes the sodium ion concentration in the solution to rise sharply, and the high concentration of Na + enters the three-dimensional network structure of the material, making the material more likely to approach and promoting the formation of disulfide bonds.
[0058] Four, application effect of saline-alkali soil improvement 1. Flocculation behavior of heavy saline-alkali soil To verify the effect of the prepared saline-alkali soil improvement material on soil aggregates, a small test tube flocculation and sedimentation experiment was designed. The lower the turbidity, the faster the surface soil particles settle, the better the soil aggregate flocculation effect, and the stronger the performance of the improvement material. Nine treatments were set up, namely CK (no soil improvement material added), addition of 0.1wt% of the saline-alkali soil weight of the lignin-based saline-alkali soil improvement materials of Examples 1-3 and Comparative Examples 1-5. In a 50 mL test tube, 5 g of saline-alkali soil (saline-alkali soil taken from the surface soil (0-15 cm) of Kenli County, Dongying City, Shandong Province (north latitude 37°70', east longitude 118°85'), sieved to 2 mm, air-dried, pH value 8.6, EC value 9.6 ms / cm, soil sodium ion content 5.32 mg / g) was added, then 45 mL of deionized water was added, and the mixture was vigorously shaken for 90 s and then left to stand. The turbidity of the supernatant of the soil after 5 min was tested as shown in Figure 8 .
[0059] As shown in Figure 8 , the average turbidity of the supernatant of the control group (CK) was 264.67 NTU, indicating that in the absence of the addition of the improvement material, the saline-alkali soil had strong dispersibility in water, and soil aggregates were difficult to form, resulting in a high turbidity of the supernatant. In comparison, the average turbidity of the supernatant of Examples 1-3 was significantly lower than that of the CK group, with Example 1 being the best, with a turbidity reduction of 91.96% compared to CK.
[0060] Compared with Comparative Examples 1 and 2, Example 1 uses a process of distribution activation and alternating copolymerization, avoiding the problem of segment mixing of AMPS and DMC due to large difference in reactivity ratio when synchronously feeding, thereby realizing a more uniform alternating copolymerization structure. This structure enables the material to simultaneously adsorb negatively charged clay particles and positively charged iron oxide and humus on the same molecular chain, forming a "patch-charge neutralization" and "bridging" dual mechanism synergistic effect, effectively solving the problem of high dispersion of saline-alkali soil particles.
[0061] Comparative Example 3 differs from Examples 1-3 in that itsaconic acid is used instead of 2-acrylamido-2-methylpropanesulfonic acid (AMPS), and the supernatant turbidity decreases by only 39.55% compared to CK, which is much lower than the effect of Examples 1-3. This shows that the polymerization efficiency of itaconic acid is low due to the large steric hindrance, and the subsequent introduction of mercapto groups is not ideal, and the hydration radius of the carboxylic acid group is smaller than that of the sulfonic acid group, which affects the flocculation performance of the aggregates.
[0062] Comparative Examples 4 and 5 only introduce anionic or cationic monomers, respectively, and due to the inability to achieve the synergistic effect of positive and negative charges, the soil flocculation effect is significantly reduced.
[0063] 2. Severe saline soil structure improvement experiment In this experiment, PVC pipes with a diameter of 5 cm, a height of 20 cm, and perforated bottoms were used to perform soil column leaching experiments to verify the improvement effect of the material on soil permeability and sodium ion removal rate. Two layers of gauze were placed at the bottom of each column and about 1 cm thick quartz sand was laid to prevent soil from seeping out, and a 200 mL beaker was placed below the soil column to collect the leachate. Five treatments were set up: a control group CK, and the addition of 0.01% of the lignin-based saline soil improvement material prepared in Examples 1, 2, Comparative Example 1, and Comparative Example 3 to the soil, with each treatment repeated three times. Air-dried soil (topsoil (0-15 cm) taken from Dongying City, Kenli County, Shandong Province (North Latitude 37°70', East Longitude 118°85'), sieved to 2 mm, air-dried, pH value of 8.81, EC value of 9.6 ms / cm, soil sodium ion content of 5.32 mg / g) was mixed with the saline soil improvement material. 300g of mixed soil sample was divided into three times and placed into the soil column, and each time was naturally compacted. Start irrigating the soil with 90 mL of deionized water, place the soil column at room temperature for 2 days to allow the saline soil improvement material to fully react with the soil, then perform leaching experiments with deionized water. Add 90 mL of water at once, observe and record the water outflow time at the bottom of the soil column and directly measure the volume of the leachate with a graduated cylinder. When no liquid flows out of the soil column within 30 minutes, it is considered that the leaching is complete, and the total infiltration time is recorded. After leaching, the soil was poured out and air-dried to measure the soil conductivity EC and the Na + concentration in the soil.
[0064] Examples 1, 2, Comparative Example 1, and Comparative Example 3 had no significant effect on the infiltration time and leachate volume, and the soil conductivity EC and Na Figure 9The soil infiltration time of Example 1 and Example 2 is significantly shortened compared with the control group CK, and the soil infiltration time is reduced by 39.32%, and the leaching liquid volume is increased by 3%-8%. This is because the addition of the modified material improves the soil aggregate structure and increases the soil porosity, thereby improving the water infiltration efficiency. The modification effect of Comparative Example 1 and Comparative Example 3 is relatively weak, and the infiltration time is not significantly shortened and the leaching liquid volume is not significantly changed, indicating that the ability of the modified material to improve the soil permeability and soil structure is limited.
[0065] Table 2 shows the soil EC value and sodium ion content. As can be seen from Table 2, the soil EC value after treatment of Example 1-2 is significantly reduced, and is reduced by 66.11% and 54.27% respectively. The water-soluble Na + content in the soil is reduced by 56%-67.69%, indicating that the sodium ion removal effect of Example 1-2 on saline-alkali soil is significant. In contrast, the EC value of Comparative Example 1 and Comparative Example 3 is reduced by 16.92% and 24.42% respectively, and the Na + content is reduced by 32.63% and 18.18%, which is significantly lower than that of Example.
[0066]
[0067] 3. Corn potting experiment A corn planting potting experiment was used to verify the effect of the lignin modified material. The soil was taken from the topsoil (0-15 cm) of Kenli County, Dongying City, Shandong Province, and was sieved to 2 mm, air-dried, and had a pH value of 8.7 and an EC value of 3.11 ms / cm. Five treatments were set: a control group CK, and lignin-based saline-alkali soil modification materials prepared by adding 0.01% of the soil mass of Example 1, Example 2, Comparative Example 1 and Comparative Example 3, each treatment was repeated three times.
[0068] The lignin-based saline-alkali soil modification material was mixed with 1.2 kg of soil, and filter paper was placed at the bottom of the pot. 1 kg of the above soil was placed in the pot. 480 mL of deionized water was added to each pot before planting. After 2 days, 3 corn seeds (variety "Zhengdan 958", Hebei Maohua Seed Industry Co., Ltd.) were planted in each pot, and the remaining 200 g of mixed soil sample was placed on top of the seeds. After 7 days of growth, thinning was performed, and 1 plant with relatively uniform growth was retained in each pot. Water was added every 3 days after the seeds germinated, and no fertilizer was applied during the entire growth period. After 30 days of culture, the relevant indicators were measured. Table 3 shows the effect of the lignin-based saline-alkali soil modification material on the dry weight, fresh weight and plant height of corn seedlings, and Table 4 shows the effect of the lignin-based saline-alkali soil modification material on the proportion of soil microaggregates.
[0069] As shown in Table 3, the fresh weight, dry weight and plant height of Example 1 were significantly increased by 39.19%, 41.52% and 31.36% respectively compared with CK, which indicated that the lignin-based soil amendment could promote the growth of corn seedlings and reduce soil salinity to create a more suitable environment for corn root elongation.
[0070]
[0071] Further, the composition of soil water-stable aggregates was analyzed by wet sieving method, and the results are shown in Table 4. As shown in Table 4, compared with CK, the proportion of aggregates with a particle size greater than 0.25 mm in Example 1 and Example 2 was significantly increased by 47.91% and 37.3% respectively. This indicated that the dual-response lignin-based saline-alkali soil amendment could enhance the stability of aggregates, effectively improve the soil structure and optimize the soil physical environment.
[0072]
[0073] Figure 10 The effects of the lignin-based saline-alkali soil amendment on the properties of the potting soil are shown in Table 6. Figure 10 As shown in Table 6, compared with CK, the soil pH, EC value and sodium ion concentration of Example 1 and Example 2 were decreased. Among them, the soil pH was decreased from 8.44 of CK to 8.19 and 8.10 respectively; the EC value was significantly decreased by 58.81% and 43.29% respectively; and the Na+concentration was also decreased to 43.52% and 33.21% respectively. This result indicated that the lignin-based saline-alkali soil amendment could reduce the soil pH, reduce the accumulation of salt and Na+enrichment degree, effectively alleviate the growth inhibition of corn seedlings under salt stress, and thus promote the growth of corn seedlings. + +
[0074] 4. Salinization seed germination experiment A 25 mmol / L NaCl solution was used to simulate a salt stress environment, and three treatments were set, namely CK, 0.5wt% lignin-based saline-alkali soil amendment of Example 1 and Example 2, to obtain a mixed solution. In the germination test, the surface of cucumber seeds was disinfected with sodium hypochlorite for 10 min, 10 seeds were placed in a culture dish containing filter paper, and 10 mL of the above mixed solution was moved to the filter paper. After 4 days, the germination rate (GR) and average bud length (ABL) of the seeds were measured, and the results are shown in Table 5. As shown in Table 5, under the simulated salt stress conditions, the 0.5wt% lignin soil amendment could significantly improve the germination rate and bud length of cucumber seeds, effectively alleviate the inhibition of salt on seed germination, and showed good salt stress relief effect.
[0075] .
Claims
1. A method for preparing a lignin-based saline-alkali land improvement material, characterized in that: The preparation method includes the following steps: Lignin and / or lignin derivatives are modified by aqueous solution polymerization with sulfonic acid anionic monomers and quaternary ammonium salt cationic monomers to obtain an amphiphilic anionic-cationic lignin composite system solution. By introducing polythiol monomers using click chemistry, lignin-based saline-alkali soil improvement materials are prepared.
2. The preparation method according to claim 1, characterized in that: The lignin derivative is at least one of calcium lignin sulfonate, sodium lignin sulfonate, magnesium lignin sulfonate, potassium lignin sulfonate, ammonium lignin sulfonate, alkali lignin, sulfate lignin, groundwood lignin, alkylated lignin, aminoated lignin, hydroxymethylated lignin, acetylated lignin, and oxidized lignin. The sulfonic acid anionic monomer is at least one of 2-acrylamido-2-methylpropanesulfonic acid, acrylamide tert-butylsulfonic acid, 2-(methacryloyloxy)ethyldimethyl-(3-sulfopropyl)ammonium hydroxide, sulfopropyl methacrylate, sodium methpropylene sulfonate, sodium propylene sulfonate, sodium 3-allyloxy-2-hydroxypropanesulfonate, potassium 3-sulfopropyl acrylate, potassium sulfopropyl methacrylate, sodium vinyl sulfonate, and sodium p-styrene sulfonate. The quaternary ammonium salt cationic monomer is at least one of the following: methacryloyloxyethyltrimethylammonium chloride, dimethyl diallyl ammonium chloride, acryloyloxyethyltrimethylammonium chloride, methacrylamidopropyltrimethylammonium chloride, benzylvinyltrimethylammonium chloride, methacryloyloxyethyldimethylbenzylammonium chloride, N-decyl-N,N-dimethylbenzylammonium chloride, 2-acrylamidoethyldimethyldodecylammonium bromide, allyltrimethylammonium chloride, and hydroxypropyltrimethylammonium chloride chitosan; The polythiol monomer is at least one of trimethylolpropane tris(3-mercaptopropionic acid), pentaerythritol tetra(3-mercaptopropionic acid) ester, ethylene glycol di(3-mercaptopropionate), trimethylolpropane tris(2-mercaptoacetate), pentaerythritol tetramercaptoacetate, and dipentaerythritol hexa(3-mercaptopropionate).
3. The preparation method according to claim 1, characterized in that: The preparation method includes the following steps: S1. Adjust the pH of the lignin and / or lignin derivative solution and heat it; divide the quaternary ammonium salt cationic monomer solution into two equal parts by volume, and add one part to the lignin and / or lignin derivative solution; divide the oxidant and reducing agent solutions into three equal parts by weight, add one part of the oxidant solution to the above solution, and then add one part of the reducing agent solution, and react. S2. Divide the sulfonic acid anion monomer solution into two equal parts by volume. Add one part of the sulfonic acid anion monomer solution to the system obtained in S1 and react. Then add the other part of the quaternary ammonium salt cationic monomer solution, add one part of the oxidant solution, add one part of the reducing agent solution, and finally add the other part of the sulfonic acid anion monomer solution and react. The resulting anion-cationic lignin composite system solution is obtained. S3. Mix the multi-thiol monomer solution and the anion-cationic lignin composite system solution, add one part of oxidant solution and then one part of reducing agent solution, react, and after drying, obtain the lignin-based saline-alkali land improvement material.
4. The preparation method according to claim 3, characterized in that: The mass percentage concentration of the lignin and / or lignin derivative is 5%-35%; The quaternary ammonium salt cationic monomer solution has a mass percentage concentration of 60%-80%; the solvent for the quaternary ammonium salt cationic monomer solution is water. The oxidant is at least one of ammonium persulfate, potassium persulfate, sodium persulfate, and hydrogen peroxide; The reducing agent is at least one of ascorbic acid, sodium bisulfite, sodium sulfite, and sodium thiosulfate; The mass percentage concentration of the oxidant and reducing agent solution is 3%-15%; The sulfonic acid anion monomer solution has a mass percentage concentration of 30%-65%; the solvent for the sulfonic acid anion monomer solution is water. The mass percentage concentration of the polythiol monomer solution is 3.5%-30%; the solvent of the polythiol monomer solution is an ethanol solution. The ratio of the total mass of the sulfonic acid anionic monomer and the quaternary ammonium salt cationic monomer to the mass of the lignin and / or lignin derivative is 2-16:1; The mass ratio of the sulfonic acid anionic monomer to the quaternary ammonium salt cationic monomer is 1:8 to 8:1; The total mass of the oxidizing agent and reducing agent is 0.5%-5% of the total mass of the lignin and / or lignin derivatives, quaternary ammonium cationic monomers, sulfonic acid anionic monomers and polythiol monomers; The mass ratio of the oxidant to the reducing agent is 1:1-1.5; The mass ratio of lignin and / or lignin derivatives to polythiol monomers is 5-15:
1.
5. The preparation method according to claim 4, characterized in that: When the mass ratio of the sulfonic acid anionic monomer to the quaternary ammonium salt cationic monomer is in different ranges, the lignin-based saline-alkali soil improvement material exhibits drastically different macroscopic physical states: When the mass ratio of the sulfonic acid anionic monomer to the ammonium salt cationic monomer is 1:1.5 to 1.5:1, the lignin-based saline-alkali soil improvement material forms a stretchable gel state. When the mass ratio of the sulfonic acid anionic monomer to the ammonium salt cationic monomer is between 1:1.5 and 1:8 (excluding 1:1.5), the lignin-based saline-alkali soil improvement material forms a high-viscosity aqueous solution. When the mass ratio of the sulfonic acid anionic monomer to the ammonium salt cationic monomer is between 1.5:1 and 8:1 (excluding 1.5:1), the lignin-based saline-alkali soil amendment material forms a low-viscosity aqueous solution.
6. The preparation method according to claim 3, characterized in that: In step S1, the pH of the lignin and / or lignin derivative solution is adjusted to 10-12 using KOH solution; The heating temperature is 35-50℃; The reaction time is 1-2 hours; In step S2, a portion of sulfonic acid anionic monomer solution is added to the system obtained in S1, and the reaction time is 1-2 hours. After adding another portion of the sulfonic acid anion monomer solution, the reaction time is 1-2 hours. In step S3, the reaction time is 2-4 hours.
7. The preparation method according to claim 3, characterized in that: In steps S1, S2 and S3, the oxidizing agent solution is added dropwise for 30 minutes, followed by the addition of the reducing agent solution. In step S3, the multi-thiol monomer solution is added dropwise to the anion-cation lignin composite system solution at a flow rate of 0.5-15 mL / min.
8. The lignin-based saline-alkali land improvement material prepared by the preparation method according to any one of claims 1-7.
9. The application of the lignin-based saline-alkali soil amendment material according to claim 8 in the improvement of saline-alkali soil.
10. The application according to claim 9, characterized in that: Based on the different mass ratios of the sulfonic acid anionic monomer and the quaternary ammonium salt cationic monomer, and the lignin-based saline-alkali soil improvement material obtained after reaction with the polythiol monomer, the following application methods and dosages are adopted: 1) When the mass ratio of the sulfonic acid anionic monomer to the quaternary ammonium salt cationic monomer is 1:1.5 to 1.5:1, it can be applied directly to the soil as a soil conditioner or used as a coating material; wherein, the application rate of the soil conditioner is 40-200 kg / mu, and the application rate of the coating material is 3%-20% of the total mass of the coating fertilizer. 2) When the mass ratio of the sulfonic acid anionic monomer to the quaternary ammonium salt cationic monomer is 1:8 to 1:1.5, the resulting material is prepared as an aqueous solution for foliar spraying or drip irrigation; for foliar spraying, the concentration is prepared at 0.5%-2%, and the dosage is 20-50 kg / mu; for drip irrigation, the concentration is prepared at 0.01-2%, and the dosage is 20-150 kg / mu. 3) When the mass ratio of the sulfonic acid anionic monomer to the quaternary ammonium salt cationic monomer is between 1.5:1 and 3:1, the resulting material is used as a root-dipping agent for seedlings. When using it, dilute it to a mass concentration of 0.1% to 0.3%, soak the crop roots in the solution for 5 minutes, and then plant it.
Citation Information
Patent Citations
Bio-based amphoteric polymer as well as preparation method and application thereof
CN113831480A
Material for removing sodium ions in saline-alkali soil and preparation method
CN120459954A
Preparation method of lignin biomass resin-based saline-alkali soil improver
CN112537989A
Soil conditioner and preparation method thereof
CN115772267A
Alumina red mud flocculant and preparation method thereof
CN118255946A
Cited By
Lignin branched modified coal washing flocculant and preparation method thereof
CN121537577A
Water-reducing water-soluble fertilizer and preparation method thereof
CN121609603A